Early predictors of language outcomes in Down syndrome: A mini-review - Filipe, Marisa G.; Cruz, Sara; Veloso, Andreia S.; Frota, Sónia (Frontiers in Psychology, 2022)
As children with Down Syndrome (DS) typically manifest significant delays in language development, research has pointed out predictors of later language skills for this clinical population. The purpose of this study was to systematically explore the evidence for early predictors of language outcomes in infants and toddlers with DS from studies published between 2012 and 2022. After the search, nine studies met the inclusion criteria. Results indicated that maternal educational level, adaptive level of functioning, cognitive function, attention skills, communicative intent of the child, early vocalizations, gestures, baby signs, parents’ translation of their children's gestures into words, and vocabulary level are significant predictors of language outcomes in children with DS. These findings provide a timely and warranted summary of published work that contributes to current understanding of the development of language and communication in DS. They are therefore useful to researchers, clinicians, and families.